2020
DOI: 10.1097/jhq.0000000000000274
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Burnout Predicts Self-Reported Medication Administration Errors in Acute Care Hospitals

Abstract: Background: Every one out of 10 nurses reported suffering from high levels of burnout worldwide. It is unclear if burnout affects job performance, and in turn, impairs patient safety, including medication safety. The purpose of this study is to determine whether nurse burnout predicts self-reported medication administration errors (MAEs). Methods: A cross-sectional study using electronic surveys was conducted from July 2018 through January 2019, using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…These factors include employee fatigue, lack of medication knowledge, and inattention 27,28 . Employee fatigue or burnout may lead to a nurse being distracted during the medication administration process, increasing the risk of an error 28,33 . If a nurse is unfamiliar with a medication, there is an increased risk of a medication error 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors include employee fatigue, lack of medication knowledge, and inattention 27,28 . Employee fatigue or burnout may lead to a nurse being distracted during the medication administration process, increasing the risk of an error 28,33 . If a nurse is unfamiliar with a medication, there is an increased risk of a medication error 27 .…”
Section: Resultsmentioning
confidence: 99%
“…There is some variation within each healthcare environment, so it is integral for leadership to identify the gaps in care delivery within their respective environments. Engaging the nursing staff to determine environmental factors contributing to MAE and inquiring about feasible measures to implement for preventing MAEs, including heightened adherence to safety practices, is key to sustainability 33,34 . Using this concept analysis may help guide the study of the healthcare environment and determine empirical measures to assess a MAE's impact.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is no other study assessing the relation between ACEs and burnout in such a broad sample of different healthcare professions. Given the important implications of burnout among healthcare professionals, including increased risks for medical errors and suicidal thoughts (Brown et al, 2009 ; Montgomery et al, 2021 ; Patel et al, 2018 ; van der Heijden et al, 2008 ), there is a need for targeted support. Particularly, as the risk for burnout is generally high in healthcare professions (Martini et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research data suggest that healthcare professionals have already been at high risk for burnout before the COVID-19 pandemic (Martini, Arfken, Churchill, & Balon, 2004 ). This, in turn, has been shown to result in an increased risk for medical errors in healthcare professionals and decreased patient satisfaction with patient–physician interaction (Montgomery et al, 2021 ; Patel, Bachu, Adikey, Malik, & Shah, 2018 ; Wang et al, 2014 ; Weigl et al, 2015 ). Healthcare professionals with burnout are at higher risk for disruptive behaviour (Brown, Goske, & Johnson, 2009 ) and suicidal thoughts (van der Heijden, Dillingh, Bakker, & Prins, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another report revealed that hospital staff nurses working at night duty shift often lack experience and interruption could cause high MEs rates [21]. Although 12hour shifts usually start at 7 p.m. and end at 7 a.m., some shifts start at 3 a.m. and end at 3 p.m.…”
Section: Background and Related Workmentioning
confidence: 99%